Dynamic Relationship Between Residential Prices and Stock Prices in New Zealand - Pham, Vu Anh (Auckland University of Technology, 2017)
The purpose of this dissertation is to examine the relationship between house prices and stock prices in New Zealand, using quarterly data from 1990 to 2016. Employing Cointegration and Granger Causality tests, Variance Decomposition and Impulse Response Function, this study finds that while the two markets are generally segmented, there is some weak evidence showing that house prices lead stock prices in short-term and stock prices lead the house prices over long-run.
Keywords: Housing; Residential; Stock; New Zealand; Granger Causality; Wealth effect; Credit price effect